2000
DOI: 10.4314/sajas.v30i2.3858
|View full text |Cite
|
Sign up to set email alerts
|

The effect of choice-feeding from 7 weeks of age on the production characteristics of laying hens

Abstract: Day-old Amberlink pullets were fed chicken starter mash for the first seven weeks of age. Group A was choice-fed with pelleted protein concentrate, whole yellow maize and limestone powder from seven to 16 weeks of age. Group B received the same diet as group A, but the protein concentrate was fed in mash form. Group C (control treatment) received a pullet grower diet in mash form. The pullets were placed in individual laying cages from 16-80 weeks of age. The choicefed groups received feedstuffs from three sep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
4
1

Year Published

2006
2006
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 15 publications
1
11
4
1
Order By: Relevance
“…This result is different from other studies (Olver and Malan, 2000;Dana and Ogle, 2002), which showed lower DM intake by choice-fed birds compared to those that received a complete layer mash. This can be explained in our study by the anti-nutritional factors, such as a trypsin inhibitor and tannins, present in the mixed feed owing to the high level of inclusion (50%) of cowpea, which would probably have reduced its palatability (Pusztai et al, 1992).…”
Section: Effect Of Supplementation On Feed and Nutrient Intakecontrasting
confidence: 99%
See 1 more Smart Citation
“…This result is different from other studies (Olver and Malan, 2000;Dana and Ogle, 2002), which showed lower DM intake by choice-fed birds compared to those that received a complete layer mash. This can be explained in our study by the anti-nutritional factors, such as a trypsin inhibitor and tannins, present in the mixed feed owing to the high level of inclusion (50%) of cowpea, which would probably have reduced its palatability (Pusztai et al, 1992).…”
Section: Effect Of Supplementation On Feed and Nutrient Intakecontrasting
confidence: 99%
“…This can be explained in our study by the anti-nutritional factors, such as a trypsin inhibitor and tannins, present in the mixed feed owing to the high level of inclusion (50%) of cowpea, which would probably have reduced its palatability (Pusztai et al, 1992). This negative effect on palatability due to the presence of cowpea was confirmed by the significantly lower intake of cowpea in favour of maize in all the choice-fed groups, although it should be pointed out that a high intake of maize is usually seen when it is given separately (Olver and Malan, 2000;Dana and Ogle, 2002).…”
Section: Effect Of Supplementation On Feed and Nutrient Intakementioning
confidence: 95%
“…Many factors, e.g. manipulation of time of access to some nutrients,1, 2 quantitative3–5 or qualitative6, 7 feed restriction and choice feeding8–10 in the starter, grower and/or developer phases, have been reported to affect the growth curve, early egg weight and sexual maturity of pullets and consequently egg production. Therefore favourable genetic characteristics can only be achieved when the bird is provided with all its nutritional requirements 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…Birds have specific appetites for nutrients such as energy, protein and calcium 10, 11, 14. Also, the nature of feedstuffs and the form of protein source are very important factors affecting the pattern of feed intake and the performance of choice‐fed birds.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation